Biodegradable Silk Fibroin Nanocarriers to Modulate Hypoxia Tumor Microenvironment Favoring Enhanced Chemotherapy - Bin, Li; Yang, Yuxiao; Wang, Feiyu; Wang, Rong; Fei, Hongxin; Duan, Siliang; Huang, Linling; Liao, Na; Zhao, Shimei; Ma, Xinbo (Frontiers in Bioengineering and Biotechnology, 2022)
Biopolymer silk fibroin (SF) is a great candidate for drug carriers characterized by its tunable biodegradability, and excellent biocompatibility properties. Recently, we have constructed SF-based nano-enabled drug delivery carriers, in which doxorubicin (Dox) and atovaquone (Ato) were encapsulated with Arg-Gly-Asp-SF-Polylactic Acid (RSA) to form micellar-like nanoparticles (RSA-Dox-Ato NPs). The RGD peptide was decorated on micellar-like nanoparticles, promoting tumor accumulation of the drug. Meanwhile, Ato, as a mitochondrial inhibitor, would reverse the hypoxia microenvironment and enhance chemotherapy in the tumor. In vitro, the biopolymer alone showed extremely low cytotoxicity to 4T1 cell lines, while the RSA-Dox-Ato demonstrated a higher inhibition rate than other groups. Most significantly, the ROS levels in cells were obviously improved after being treated with RSA-Dox-Ato, indicating that the hypoxic microenvironment was alleviated. Eventually, SF-based targeted drug carrier provides biocompatibility to reverse hypoxia microenvironment in vivo for enhancing chemotherapy, strikingly suppressing tumor development and thereby suggesting a promising candidate for drug delivery system.